2002
DOI: 10.1016/s0014-5793(02)03678-5
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of in vivo induced cheY‐4 gene of Vibrio cholerae in motility, early adherence to intestinal epithelial cells and regulation of virulence factors

Abstract: Using a global transcription pro¢le approach cheY-4 of Vibrio cholerae was identi¢ed as an in vivo induced gene. In the present study, duplication of the gene in the chromosome resulted in increased motility, increased chemotactic response towards isolated intestinal mucus layer and stronger adhesion to human intestinal epithelial cell line at an early phase of infection compared to wild type and a null mutant strain. In contrast to the cheY-4 null mutant, duplication of cheY-4 gene resulted in increased expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 22 publications
1
28
0
Order By: Relevance
“…Another possibility is that the modulated chemotaxis is due to varied gene expression regulated by CheY4. Indeed, the duplication of cheY4 increases the expression levels of ctxAB and tcpA (3). It has also been reported that motility and the expression of ctxAB are inversely regulated by bile (13).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Another possibility is that the modulated chemotaxis is due to varied gene expression regulated by CheY4. Indeed, the duplication of cheY4 increases the expression levels of ctxAB and tcpA (3). It has also been reported that motility and the expression of ctxAB are inversely regulated by bile (13).…”
Section: Discussionmentioning
confidence: 94%
“…Nonchemotactic mutants with counterclockwise-and clockwise-biased flagellar rotation were reported to show enhanced and attenuated infectivity, respectively (6). In an in vitro study (3), cells lacking or overproducing CheY4 exhibited a decreased or increased production of CT, respectively, and CheY4 was suggested to be involved in attachment to host cell layers and migration toward ingredients of the intestine. It was also reported that two MLPs (TcpI and AcfB) are involved in colonization (9,15) and that another MLP (HlyB) is involved in the secretion of hemolysin (1,18).…”
mentioning
confidence: 99%
“…The bacterium inhabits nutrient-poor aquatic environments such as rivers and estuaries or occasionally intrudes into the nutrient-rich lumen of the human gastrointestinal tract (38). Chemotaxis of V. cholerae toward favorable locations is proposed to play critical roles in its survival (6) and pathogenicity (2,5,8,13,14,15,16,17,20,21,30,31). However, the external signals and cellular factors that mediate chemotaxis of V. cholerae are only poorly understood.…”
mentioning
confidence: 99%
“…Phospho-CheY then interacts with the C-ring of the flagellum, which causes a reversion from CCW to CW rotation, resulting in a change of swimming direction. CheB and CheW are involved in modulating the signal transduction pathway (Freter and O'Brien 1981;Alm and Manning 1990;Everiss, Hughes et al 1994;Harkey, Everiss et al 1994;Lee, Butler et al 2001;Banerjee, Das et al 2002;Hyakutake, Homma et al 2005). …”
Section: Chemotaxis and Virulencementioning
confidence: 99%